Design gramofonu - Maca, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Cílem této bakalářské práce je návrh designu gramofonu. Návrh vychází z důkladné analýzy problematiky a opírá se o poznatky získané v rešeršní části práce. Gramofon by měl působit jako vhodný doplněk moderního interiéru a splňovat správné technické i ergonomické parametry.

The goal of this bachelor thesis is design of gramophone. Design is based on a close analysis of problems and is based on a knowledge gained in the search part. Turntable should act as a suitable complement in modern interior and meet the right technical and ergonomic characteristics.
Design of gramophone
Keywords: Gramofon; design; zvuk; konstrukce; Gramophone; design; sound; construction